Secondary postpartum haemorrhage in a tertiary care hospital of North India: a retrospective analysis - Nigeen, Waseeqa; Farooq, Mariya; Afzal, Asima; Ashraf, Sameena; Bhat, Abdus Sami (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum haemorrhage (PPH) is a very common complication that follows delivery. It is one of the leading causes of maternal mortality both in developing and developed countries. Primary PPH has been studied a lot, but data regarding secondary PPH is sparse. Our objective was to study the clinical characteristics and outcome of patients presenting with secondary PPH Methods: A retrospective descriptive study done at Lalla Ded hospital Srinagar, a tertiary care hospital of North India, between June 2015 and December 2015. Results: Fifty patients with secondary PPH were studied out of whom 36 were delivered outside this hospital and referred. Fourteen patients who delivered in this hospital developed secondary PPH. Mean age of patients was 35±3 years. Retained products of contraception (RPOCs) was the leading cause in 36 (72%) of patients followed by endometritis in ten (20%). Mean hemoglobin concentration was 8.7±1.9grams ranging from 4.4 grams to 12.9 grams. Mean hospital stay was 6.3±1.5 days ranging from 1 day to 20 days. Curettage was done in 40 (80%) of patients including 36 having RPOC s and check curettage in four patients. Fourteen (28%) patients required blood transfusion. One patient required hysterectomy. None of the patients died. Conclusions: Secondary PPH has been studied very little. Our results show retained products of contraception as a leading cause of secondary PPH which is probably related to poor management of third stage of labour. There is crucial role of active management of third stage of labour in preventing secondary PPH. Majority of secondary PPH patients require dilatation and curettage with other supportive measures only. Surgical intervention is rarely required. Blood loss is usually mild to moderate. Prognosis is good if medical intervention is sought early.